Effect of the direct exchange interaction between magnetic impurities on magnetization in diluted magnetic semiconductors - Thai, Vu Kim; Anh, Le Duc; Tuan, Hoang Anh (Communications in Physics, 2012)
We consider a model of III-V diluted magnetic semiconductors where both of the exchange interaction between carrier and impurity spins, and the direct exchange interaction between magnetic impurities are taken into account. The magnetization as a function of temperature for a wide range of model parameters is calculated and discussed. We show that for a degenerate carrier system the suppression of the magnetization is sensitive to the antiferromagnetic coupling constant and the impurity concentration.